The Leadership of Among Principals in Strengthening Education Management to Improve Quality at SMA Negeri 1 Pengasih - Untung Maryadi; Pardimin Pardimin; Saryanto Saryanto (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the application of Among Leadership in strengthening education management to improve the quality of learning at SMA Negeri 1 Pengasih. Among leadership, which is rooted in the thought of Ki Hajar Dewantara, emphasizes the principles of Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani. This research uses a qualitative approach with a phenomenological method that focuses on the experience of principals and teachers. The results of the study show that Among Leadership is implemented through strengthening human resource management, curriculum development, and school-to-community relations. The results of the study show that the among leadership applied by the principal of SMA Negeri 1 Pengasih is realized through three main principles, namely in the role of the principal which is reflected in the example of the principal in discipline, responsibility, and concern for the teaching and learning process, in the middle of Mangun Karsa which is seen in the efforts of the principal to empower teachers and education personnel through a participatory approach in managerial decision-making, As well as Tut Wuri Handayani which is implemented by providing freedom of responsibility to school residents to innovate in education management. The principal acts as a role model, facilitator, and supporter who encourages teacher participation and creates a collaborative culture. In conclusion, Among Leadership is effective in increasing teacher motivation and professionalism which has an impact on improving the quality of learning. This research makes a theoretical and practical contribution to the development of local values-based educational leadership.